Expanding and shifting trends in carbon market research: a quantitative bibliometric study. (15th September 2015) - Du, Huibin; Li, Bingli; Brown, Marilyn A.; Mao, Guozhu; Rameezdeen, Raufdeen; Chen, Hao
Abstract: This paper examined the carbon market literature from 1992 to 2011 using bibliometric techniques based on the database of Science Citation Index (SCI) and Social Science Citation Index (SSCI). Of 5809 publications, 82% were journal articles. Our analysis documents that carbon market publications are expanding rapidly. Based on the contribution of countries and their h-index, the US has published most and been most influential in this area, followed by the UK, Canada, Germany and China. The Chinese Academy of Sciences (120), US Forestry Service (70) and University of Maryland (68) were the most productive research institutes. The most common subject category, Environment Sciences (1551), experienced an exponential increase with an average growth rate of about 50%, and the most productive journal was Energy Policy (469). According to the analysis of keywords, the hotspots related to carbon markets were "global warming" and "carbon tax" in the 1990's, but "climate change" and the "clean development mechanism" superceded them in the most recent decade. The most cited article published in Science in carbon market research is presented. This analysis is not only helpful for policymakers and others to understand trends in the field, but may also influence researchers' selection of future studies. Highlights: Carbon market literature from 1992 to 2011 in the SCI and SSCI. Bibliographic analysis of general pattern, journal, subject, h-index, etc. Cooperation among countries or institutions studied by social network analysis. High cited articles given from 1992 to 2011. Global hotspots are found to influence researchers' selection of future studies.